Inequality and Institutions - Chong, Alberto; Gradstein, Mark (The Review of Economics and Statistics, 2007)
This paper presents theory and evidence on the relationship between inequality and institutional quality. We exhibit a model in which the two may dynamically reinforce each other and set to test this relationship with a broad array of institutional measures. The double causality between institutional strength and a more equal distribution of income is empirically established using dynamic panel and linear feedback analysis.